Resilience zoning of Shiraz city against floods using VIKOR_AHP model - Mohammad Hadi Fattahi; Mohammad Behroozi (مهندسی منابع آب, 2023)
AbstractIntroduction: Flooding in urban areas is increasing due to population growth with improper land use planning and climate change-induced increase in extreme rainfall events. Flood risks have affected the largest proportion of the world's population (45%) compared to other natural disasters and caused 5424 recorded deaths between 2000 and 2017, and if our cities are to be resilient and better able to deal with the consequences of floods. city to cope, it is expected that they will adopt sustainable strategies to adapt to the new climatic and socio-economic conditions. Accordingly, the purpose of this research is to evaluate the resilience of Shiraz city against floods in order to identify areas of low resilience and take the necessary measures to increase it. Their resilience should be done.Methods: The research method of this research is descriptive-analytical and practical in terms of purpose. Based on the background of the research and refinement of the variables based on the conditions of the research area, four dimensions and 24 criteria were determined, including demographic (8 variables), economic (3 variables), environmental (4 variables) and infrastructure (9 variables).Findings: AHP method was used for weighting and access to critical infrastructure for action and recovery has the highest weight with a weight of 0.115, and infrastructure with a weight of 0.395 has the highest weight. The estimated CR of the model is equal to 0.07, which it shows the acceptable accuracy of the model. For zoning, the Vikor model has been used, and based on the output of the model, 9.92% of the area is in the zone with low resilience, where about 16.63% of the population of Shiraz lives in this zone, and about 75.43% of the area is in the zone with medium resilience. 74.56% of the population lives in it, and the area with high resilience is 14.65%, where 8.81% of the population of Shiraz lives.